التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات الحركية لدى تلاميذ مرحلة التعليم الابتدائي - بوقرة مسعود; Supervisor بوخرص رمضان (Mohamed Boudiaf University of M'sila, 2024)
الملخص : بالعربية(عبارة عن فقرة تهدف هذه الدراسة بشكل عام إلى ابراز دور التدريس المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات التعلم المهارات الحركية في مرحلة التعليم الابتدائي وذلك من وجهة نظر اساتذة التربية البدنية والرياضية في الطور الابتدائي، ومن أجل تحقيق أهداف بحثنا اعتمدنا على المنهج الوصفي التحليلي لأنه الأنسب لها، وشملت عينة الدراسة (28) أستاذً في المدارس والابتدائيات الموجودة في دائرة حمام الضلعة بولاية المسيلة، وتم الاعتماد على الاستبيان مكون من ستة محاور وتضمّن (20) فقرة، مقسمة على 4 محاور، وتم التأـكد من صدق الأداة وثباتها ،واستخدمنا الحزم الإحصائية spss لحساب معامل الارتباط بيرسون والمتوسط الحسابي والانحراف المعياري كوسائل إحصائية، حيث أظهرت النتائج على أن تحقق الفرضيات الجزئية كلها" تـؤكد على صحة الفرضية العامة والتي نصت على انه يمكن اعتبار التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات، كما أوصينا بضرورة إجراء دراسات مشابهة أكثر عمقا و تخصصا في أسلوب التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات التعلم المهارات الحركية في مرحلة التعليم الابتدائي عنوان الدراسة : التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات الحركية لدى تلاميذ مرحلة التعليم الابتدائي أهداف الدراسة : - التعرف على مساهمة استراتيجية فرق الألعاب التعاونية في علاج صعوبات التآزر الحركي . - التعرف على مساهمة التدريس وفق استراتيجية الحواس المتعددة في علاج قصور الانتباه . - التعرف على مساهمة استراتيجية المحطات التعليمية في علاج الصعوبات الإدراكية الحركية . - التعرف على مساهمة استراتيجية التمثيل ولعب الأدوار في تنمية الذكاء الحركي . التساؤل العام الدراسة : هل يمكن اعتبار التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات الحركية في مرحلة التعليم الابتدائي؟ التساؤلات الجزئية : 1- هل تساهم استراتيجية فرق الألعاب التعاونية في علاج صعوبات التآزر الحركي لتلاميذ مرحلة التعليم الابتدائي؟ 2- هل يسهم التدريس وفق استراتيجية الحواس المتعددة في علاج قصور الانتباه لدى التلاميذ المرحلة الابتدائية؟ 3- هل تسهم استراتيجية المحطات التعليمية في علاج الصعوبات الإدراكية الحركية لتلاميذ مرحلة التعليم الابتدائي؟ 4- هل تسهم استراتيجية التمثيل ولعب الأدوار في تنمية الذكاء الحركي لدى تلاميذ المرحلة الابتدائية؟ الفرضية العامة للدراسة : يمكن اعتبار التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات الحركية في مرحلة التعليم الابتدائي الفرضيات الجزئية 1- تساهم استراتيجية فرق الألعاب التعاونية في علاج صعوبات التآزر الحركي لتلاميذ مرحلة التعليم الابتدائي.. 2- يسهم التدريس وفق استراتيجية الحواس المتعددة في علاج قصور الانتباه لدى التلاميذ المرحلة الابتدائية. 3- تسهم استراتيجية المحطات التعليمية في علاج الصعوبات الإدراكية الحركية لتلاميذ مرحلة التعليم الابتدائي. 4- تسهم استراتيجية التمثيل ولعب الأدوار في تنمية الذكاء الحركي لدى تلاميذ المرحلة الابتدائية. المنهج المتبع في الدراسة : المنهج الوصفي............ الأدوات المستخدمة في الدراسة الاستبيان....... الكلمات المفتاحية بالعربية : التعليم المتمايز، خيار استراتيجي ، علاج ، ذوي صعوبات التعلم ، المهارات الحركية في مرحلة التعليم الابتدائي الكلمات المفتاحية بالإنجليزية : Strategic choice , treatment, ، Differentiated education difficulties in learning , Motor skills in primary education جاء هذا البحث في فصول . الفصل الأول:.الاطار العام للدراسة وتناول الفصل الثاني:التعليم المتمايز أما الفصل الثالث: ذوي صعوبات تعلم المهارات الحركية............... الفصل الرابع :منهجية الدراسة................................................ الفصل الخامس :عرض وتحليل ومناقشة النتائج الفصل السادس: الاستنتاجات والاقتراحات ، قائمة المصادر والمراجع وقائمة الملاحق. من أهم النتائج التي توصل إليها الباحث توجد علاقة إرتباطيه إيجابية ذات إحصائية بين التعليم المتمايز وصعوبات تعلم المهارات عند مستوى دلالة "0.05" ودرجة الحرية "19"، وهذه النتائج التي توصلنا إليها " تحقق الفرضيات الجزئية كلها" تـؤكد على صحة الفرضية العامة والتي نصت على انه يمكن اعتبار التعليم المتمايز كخيار إستراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات. أهم التوصيات:........ - اجراء دراسات وبحوث حول أسلوب التعليم المتمايز كخيار استراتيجي مدعم لعلاج ذوي صعوبات تعلم المهارات الحركية مرحلة التعليم الابتدائي. - اعادة بعث اقسام الامتياز - الاستثمار في المواهب الخاصة وتشجيعهم وتوجيههم Searchlight in English Institute of Science and Technology of Physical Activities and Sports. Physical education Department: Order No:........................................ No. d 'registration : 202323044094521............................................ Searcher : .bouguerra messaoud........................... ............. Publicly supported on :.11/06/2024............................................................. Title of the thesis (dissertation):.. Differentiated education as a supportive strategic option for treating those with difficulties in learning motor skills among primary school students Language of the thesis: ..ARABIC........................................................................ Model of the thesis: MASTER ................................................................ Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor: RAMDANE BOUKHORS Grade: Professor rank Lecturer Number of pages: ......75................... Option: ......WORD PDF............... Summary: This study generally aims to highlight the role of differentiated teaching as a supportive strategic option for treating people with learning difficulties and motor skills in the primary education stage, from the point of view of physical education and sports teachers in the primary stage. In order to achieve the objectives of our research, we relied on the descriptive analytical approach because it is the most appropriate for it, and it included: The sample of the study was (28) teachers in schools and primary schools located in the municipality of Hammam Dalaa t in the state of M’Sila. The questionnaire was based on six parts and included (20) items, divided into 4 parts. The validity and reliability of the tool was confirmed, and we used the spss statistical package to calculate The Pearson correlation coefficient, the arithmetic mean, and the standard deviation as statistical means, as the results showed that all the partial hypotheses were fulfilled, “confirming the validity of the general hypothesis, which states that differentiated education can be considered as a supported strategic option for treating people with difficulties in learning skills. We also recommended the necessity of conducting similar, more in-depth studies.” supportive strategic option for treating those with difficulties in learning motor skills among primary school students. Title of the study: Differentiated education as a supportive strategic option for treating those with difficulties in learning motor skills among primary school students The importance of this study: The importance of this study lies in the fact that it sheds light on one of the important teaching strategies in our current era, which is differentiated education, in view of the observed differences and the great variation in students, which requires education that keeps pace with these differences and variations. This study can also be a reference for teachers of physical education and sports and help them. In developing and improving teaching methods, especially for those who face difficulties in teaching students with learning difficulties, it would also provide effective solutions to treat this disorder and bring the educational process to the maximum degree of flexibility and mastery, and thus reach the goals assigned to it، This study may also benefit those concerned with developing curricula, by including various activities to confront differences and diversity among learners. This study may also benefit researchers in conducting further research on differentiated education and shedding light on a category of students, which is the category with learning difficulties. The purpose of the study: This study generally aims to highlight the role of differentiated teaching as a strategic option to support the treatment of people with learning difficulties and motor skills in the primary education stage, from the point of view of physical education and sports teachers in the primary stage. This study also aims to achieve the following objectives: 1- Identifying the contribution of the strategy of cooperative games teams in treating the difficulties of motor coordination for primary school students. 2- Identifying the contribution of teaching according to the multi-sensory strategy in treating attention deficit among primary school students 3- Identifying the contribution of the educational stations strategy in treating the perceptual-motor difficulties of primary school students. 4- Identifying the contribution of acting and role-playing strategies to developing motor intelligence among primary school students. Problem: Can differentiated education be considered a supportive strategic option for treating people with difficulties learning motor skills in the primary education stage? Hypotheses: -1 The strategy of cooperative games teams contributes to treating the difficulties of motor coordination for primary school students. -2 Teaching according to the multi-sensory strategy contributes to treating attention deficit among primary school students. -3 The educational stations strategy contributes to treating the perceptual-motor difficulties of primary school students. -4 The acting and role-playing strategy contributes to developing motor intelligence among primary school students. Key words : differentiated education ، difficulties learning motor skills Differentiated education , Strategic choice , treatment, ، difficulties in learning , Motor skills in primary education - The most important results achieved are: There is a positive, statistically significant correlation between differentiated education and difficulties in learning skills at a significance level of “0.05” and a degree of freedom of “19.” These results that we reached “fulfill all the partial hypotheses” confirm the validity of the general hypothesis, which states that differentiated education can be considered a strategic option. Supported for treating people with difficulties in learning motor skills
Keywords: التعليم المتمايز; خيار استراتيجي; ذوي صعوبات التعلم